Does Personal Innovativeness Drive EV Adoption? The Mediating Role of Perceived Risk among Indonesian Consumers - Bunga Ayu Ratnasari; Erna Maulina; Arianis Chan (Amkop Management Accounting Review (AMAR), 2026)
The Indonesian electric vehicle (EV) market has witnessed significant growth, yet a notable gap remains between high consumer interest and actual adoption due to psychological barriers. This study aims to investigate the determinants of EV purchase intention by examining the influence of personal innovativeness and the mediating role of perceived risk, specifically within the context of Chery electric vehicles in the Jabodetabek region. Employing a quantitative approach, data were collected from 100 respondents using purposive sampling and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that personal innovativeness has a significant positive direct effect on purchase intention and a significant negative effect on perceived risk. Conversely, perceived risk negatively impacts purchase intention. Importantly, the study confirms that perceived risk mediates the relationship between personal innovativeness and purchase intention. These results suggest that while innovativeness is a key driver of adoption, the reduction of perceived risk is crucial for converting consumer interest into actual purchases. The study provides strategic insights for automotive marketers to target early adopters and implement robust risk-reduction strategies to accelerate EV adoption.